Optimized scheme for fast mobile IPV6 handover and mobility in IEEE 802.16 network - Seyyedoshohadaei, Seyyed Masoud (2013)
The IEEE 802.16 standard defined mobility capability to cover the physical (PHY) and Medium Access Control (MAC) layer and intra-domain mobility. When the FMIPv6 is utilized for inter-domain mobility in WiMAX, reducing the handover latency and packet loss are still two major challenges in order to realize seamless handover. Long Latency is the main problem of previous schemes specially for real-time applications such voice over IP (VOIP) and video streaming. In addition,previous schemes cannot guarantee predictive mode for high speed users and handle handover in reactive mode with longer latency than predictive mode. To reduce overhead of handovers in group mobility in WiMAX network, a protocol such as Network Mobility Basic Support (NEMOBS) is required. However, utilizing NEMOBS in WiMAX network causes handover latency due to consequent layer-2 and layer-3 handover execution. This latency is not negligible for real-time applications To address these issues, this thesis proposes an Optimized Fast Handover Scheme (OFHS) and an Optimized Fast NEMO (OFNEMO) that will support inter-domain handover and network mobility in IEEE 802.16e network respectively. In OFHS, a pre-established multi-tunnel concept is adapted to prepare for handover in advance. Both link layer handover procedure in IEEE 802.16e and IP layer handover procedure in FMIPv6 are blended and the messages of both layers are interleaved effectively to reduce handover latency. This scheme uses cross layer design and cross function optimization. In OFNEMO the messages of handover procedure in both layer-2 in IEEE 802.16 and layer-3 in the NEMOBS are merged. In addition, preparation and pre-established multi-tunnel concept are used to reduce service disruption time. In both OFHS and OFNEMO, the time consuming reactive mode is eliminated and a semi-predictive mode which results in better performance is designed. Performances of proposed schemes have been evaluated through numerical timing model, cost analysis model (considering probability of predictive mode failure) and simulation scenarios through QualNet v5.0 simulator. All three evaluation methods were applied to the proposed schemes and related standard works published as RFC5270 and RFC3963 respectively. The simulation results show that the OFHS predictive mode reduces at least 6.3% of total handover time and 40% handover latency compared to RFC5270 predictive mode. Also, OFHS semi-predictive mode reduces 9% of total handover time and 72% handover latency compared to RFC5270 reactive mode. OFNEMO reduces 11% of total handover time and 91% handover latency in predictive mode, and 6% total handover time and 73% handover latency in semi-predictive mode respectively, compared to RFC3963. In addition, the proposed protocols increase probability of predictive mode which has better performance than Mreactive mode, even for high speed movement. The results demonstrate that OFHS and OFNEMO can optimize inter-domain handover procedures to achieve lower handover latency, reduced packet losses and increased probability of predictive mode. Hence, with this improvement, the OFHS and OFNEMO should be able to provide seamless communications for high speed mobile users, and support network mobility in WiMAX.